2010
DOI: 10.1002/chem.201001279
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterials from the Sea

Abstract: The ocean contains a host of macroscopic life in a great microbial soup. Unlike the terrestrial environment, an aqueous environment provides perpetual propinquity and blurs spatial distinctions. Marine organisms are under a persistent threat of infection by resident pathogenic microbes including bacteria, and in response they have engineered complex organic compounds with antibacterial activity from a diverse set of biological precursors. The diluting effect of the ocean drives the construction of potent molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
89
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(90 citation statements)
references
References 187 publications
(263 reference statements)
0
89
0
1
Order By: Relevance
“…Beginning with the introduction of penicillin, natural products have provided diverse chemical scaffolds leading to 9 of the 12 classes of antibiotics currently used in the clinic (1,8,12). The majority of these bioactive secondary metabolites are derived from terrestrial actinomycete bacteria.…”
Section: Methicillin-resistant Staphylococcus Aureus (Mrsa) Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beginning with the introduction of penicillin, natural products have provided diverse chemical scaffolds leading to 9 of the 12 classes of antibiotics currently used in the clinic (1,8,12). The majority of these bioactive secondary metabolites are derived from terrestrial actinomycete bacteria.…”
Section: Methicillin-resistant Staphylococcus Aureus (Mrsa) Infectionmentioning
confidence: 99%
“…The majority of these bioactive secondary metabolites are derived from terrestrial actinomycete bacteria. Although much less explored than terrestrial environments, the ocean has been shown to be a bountiful source of biological and genetic diversity (9) that leads to chemically novel natural products (8,12).…”
Section: Methicillin-resistant Staphylococcus Aureus (Mrsa) Infectionmentioning
confidence: 99%
“…Marine-derived metabolites, like peptides (ribosomal and non-ribosomal), alkaloids, polyketides and terpenes, have demonstrated antimicrobial and antiviral activities [13,14]. Most of marine-derived microorganisms are characterized by unique physiochemical properties, which can help them to easily adapt to extreme habitats, and to tolerate the extreme conditions like high pH, temperature, pressure, oxygen level, light, nutrients limit, salinity and osmolality [15].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical diversity may be amplified for marine natural products due to the vast biodiversity encountered in marine environments (24). Also, bioactive secondary metabolites produced by marine organisms to fight parasitic microorganisms are often very potent, since they rapidly become diluted in the environment (25). Many antimicrobial compounds with activity against M. tuberculosis have been isolated from marine organisms, although very few have moved beyond initial hit identification (23,26).…”
mentioning
confidence: 99%